Design, Synthesis and Evaluation of Fluorescent Analogues of Abscisic Acid. Issue 26 (13th July 2020) - González, Florenci V.; Bou‐Iserte, Lledó; Miguel‐López, Borja; de la Hoz‐Rodríguez, Sergio; Kersten, Christian; Sánchez‐Sarasúa, Sandra; Espinosa‐Fernández, Verónica; Sánchez‐Pérez, Ana María
Abstract: A fluorescent analogue of abscisic acid has been prepared by combining (S)‐abscisic acid (ABA) with nitrobenzoxadiazole (NBD) fluorophore using ethanol amine as a linker. Isomerization of the double bond at the side chain of abscisic acid happened during the synthesis. The resulting fluorophore analogues derived from both isomeric compounds entered cells suggesting a wide applicability of the ABA‐NBD conjugates as fluorescent probes to study ABA mechanism of action. The functional properties of the isomeric ABA‐NBD conjugates were tested in vitro, by measuring TNFα expression and nitrite concentration in LPS‐stimulated macrophages and compared with their non‐fluorescent ABA isomers. Rationalization of the results is given as supported by docking studies of the compounds with LANCL2 and PPARγ targets. Abstract : Fluorescent analogues of abscisic acid have been prepared by combining (S)‐abscisic acid (ABA) with nitrobenzoxadiazole (NBD) fluorophore. The fluorophore analogues entered cells suggesting a wide applicability as fluorescent probes to study ABA localization in cellular compartments, and in vivo distribution. The ABA‐NBD conjugates function was compared to unconjugated ABA in LPS‐stimulated macrophages. Interestingly, we found similarities and differences with ABA, suggesting that ABA derivatives represent an excellent tool to decipher ABA mechanisms of action, by dissecting the molecule interactions with the cellular components.